Canoe country flora : plants and trees of the North Woods and Boundary Waters - Stensaas, Mark (University of Minnesota Press, 2004)
The vast North Woods, a land magnificently arrayed in the deep greens of pine, spruce, and fir and the brilliant blues of crystal clear lakes, spans the area from Minnesota to Maine and from Michigan to Hudson Bay. With a little help from Canoe Country Flora, keen explorers will discover a world full of life and wonder in the plants that thrive in this beautiful lake country. Canoe Country Flora, a friendly field guide, introduces you to ninety-six of the most common trees, shrubs, wildflowers, fungi, ferns, lichens, and other plants youre likely to encounter during your travels north. Detaile.